Governance of Waste in Indonesia: Implementing Policies and Role of Local Authorities - Yusriadi, Yusriadi; Muhammad, Ybnu T; Ansar; Farida, Umi (Cendekiawan Indonesia Timur, 2023)
This research scrutinizes the array of strategies deployed in managing waste banks across Indonesia, highlighting the nation's efforts to tackle the growing challenge of waste management. By analyzing data from existing literature and documentary sources, the study aims to understand how waste banks operate within the Indonesian context thoroughly. It reveals that the success of these waste banks varies significantly across different regions, pointing to a complex interplay of factors influencing their effectiveness. The findings of this research are particularly revealing, uncovering three main factors that influence the effectiveness of waste bank management: the availability of human and financial resources, the quality of organizational communication, and the organization's overall structure. These factors are crucial in determining how well waste banks function. Regions with adequate resources and efficient communication channels better manage waste effectively.